Cyclizations of The Isothiocyanates‐Derived Azatrienes: The CuBr–Catalyzed Switching from Thiophenes to Pyrroles. Issue 43 (8th November 2018) - Tarasova, Ol'ga A.; Nedolya, Nina A.; Albanov, Alexander I.; Trofimov, Boris A.
Abstract : Azatrienes, alkyl 2‐alkoxy‐ N ‐buta‐2, 3‐dienimidothioates, prepared from isothiocyanates, lithiated alkoxyallenes, and alkyl 2‐bromoacetates, readily cyclize in the presence of CuBr to selectively give rare functionalized pyrroles in up to 82 % yield that contrasts with the base‐catalyzed cyclization of the same azatrienes affording only thiophenes. This switching becomes possible due to the preisolation of azatrienes and their further contact with CuBr (6–9 mol‐%). A synthetically convenient route to so far inaccessible densely functionalized pyrroles has been developed. Abstract : One‐pot reactions of lithiated alkoxyallenes with isothiocyanates and alkyl 2‐bromoacetates leading to isolable 1‐aza‐1, 3, 4‐trienes and/or tetrasubstituted thiophenes were investigated. The reaction conditions for selective synthesis of 1‐aza‐1, 3, 4‐trienes have been developed. A new class of rare functionalized pyrroles, alkyl 2‐[(3‐alkoxy‐1 H ‐pyrrol‐2‐yl)sulfanyl]acetates, was synthesized via CuBr‐catalyzed intramolecular cyclization of 1‐aza‐1, 3, 4‐trienes.